New Cloth Washing Technology and Machine - Heap, Yee Nean (Universiti Sains Malaysia, 2010)
National Research and Innovation Competition (NRIC) 2010, 26th - 28th May 2010 was held at Dewan Utama Pelajar, USM Main Campus, Penang, Malaysia. Organized by the Student Representative Council of Universiti Sains Malaysia.